Reallocation Effects of the Minimum Wage - Christian Dustmann; Attila Lindner; Uta Schönberg; Matthias Umkehrer; Philipp vom Berge (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2020)
In this paper, we investigate the wage, employment and reallocation effects of the introduction of a nationwide minimum wage in Germany that affected 15% of all employees. Based on identification designs that exploit variation in exposure across individuals and regions, we find that the minimum wage raised wages, but did not lower employment. At the same time, the minimum wage lead to reallocation effects. At the individual level, the minimum wage induced low wage workers (but not high wage workers) to move from small, low paying firms to larger, higher paying firms. This worker upgrading to better firms can account for up to 25% of the wage increase induced by the minimum wage. Moreover, at the regional level, average firm quality (measured as firm size or fixed firm wage effect) increased in more affected regions in the years following the introduction of the minimum wage.
Keywords: 330